Surveillance of Misinformation on Social Media of Songkhla Consumer Association - Kai-nunna, Phirakan; Ketjinda, Chalome; Sangkachat, Jutha; Sangkachat, Nalinee (Journal of Information and Learning [JIL], 2023)
This academic article aims to investigate lessons learned by the Songkhla Consumer Association from the practical perspectives of the project on networking development for surveillance and warning towards media literacy of southern Thai consumers. This article is presented in four sections: misinformation surveillance networking development, characteristics of misinformation, debunking, and warning methods for consumers. The findings consist of the following points. First, the selected volunteers from consumer networks in Phuket, Krabi, Songkhla, Satun, and Pattani have been trained in media and information literacy for collecting and addressing problems related to the surveillance of misinformation. Second, the five most commonly found types of misinformation were exaggerated advertisements of food and drugs, exaggerated advertisement of cosmetic products, online gambling, online scams, and issues related to COVID-19, which were categorized as misleading (32.8%). Third, the impact of misinformation on local communities was regarded as the first priority for checking the reliability of existing facts; the most popular information source was the Food and Drug Administration (32.0%) and banners of refutation were created for the purpose of communication with the target audience. Lastly, feedback given to the social media source of misinformation and weekly live broadcasts via Facebook were warning methods for consumers.